Engaging Fishers' Ecological Knowledge for Endangered Species Conservation: Four Advantages to Emphasizing Voice in Participatory Action Research - Wedemeyer-Strombel, Kathryn R.; Peterson, Markus J.; Sanchez, Ramon Neftali; Chavarría, Sofía; Valle, Melissa; Altamirano, Eduardo; Gadea, Velkiss; Sowards, Stacey K.; Tweedie, Craig E.; Liles, Michael J. (Frontiers in Communication, 2019)
Using social science to integrate local knowledge into conservation science can provide unique insights to conservation challenges. Especially when baseline data of a vulnerable wildlife population is deficient, these methods can help fill critical data gaps. In this study, we integrate the principals from the trinity of voice (TOV) and participatory action research (PAR) to generate baseline data on in-water habitat use of critically endangered hawksbill sea turtles (Eretmochelys imbricata) and to build mutually beneficial relationships with local stakeholders near the hawksbill’s two primary nesting grounds: mangrove estuaries in El Salvador and Nicaragua. Local stakeholders, in this study referred to as fishers, hold expert knowledge they have acquired both experientially and culturally. Using TOV to shape PAR, we invited stakeholders to use their fishers’ ecological knowledge (FEK) to enhance conservation of this at-risk species. Our results demonstrate that in addition to using FEK to produce quantifiable data (e.g., turtle habitat use), there are four advantages to emphasizing voice throughout a PAR project: 1) provides locality-specific information, 2) enhances mutual learning and leadership, 3) incorporates local experience, knowledge, and creativity, and 4) encourages local participation and commitment to the conservation challenge.